A Novel Approach for the Stability Analysis of State Dependent Differential Equation - Erman, Sertaç; Demir, Ali (Communications in Mathematics and Applications, 2016)
In this paper, we investigate the stability of a di¤erential equation with state-dependent delay under some conditions on delay term. New necessary and su¢ cient criterions are elaborated for the asymptotic stability of the di¤erential equations with state dependent delay. Moreover, the asymptotic stability of it is illustrated for a special delay function.
Keywords: Asymptotic stability; State depended delay; Delay di¤erential equation